Analisa Pelanggaran Etika Profesi Akuntansi Studi Kasus PT Kimia Farma Tbk - Ayu, Mutiara; Ansori, Fatimah Azzahra Putri; Ni’matul Maula, Risma; Zubaidah; Saridawati (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The accounting profession plays a pivotal role in ensuring the financial stability of organizations and in delivering reliable financial information through financial statements. Ethical conduct within the profession is essential to uphold public confidence in the accuracy and transparency of corporate financial reporting. Integrity, objectivity, professional competence and due care, confidentiality, and professional behavior in line with established accounting standards are the fundamental ethical principles in accounting that both individuals and organizations must continually uphold. This study aims to examine ethical violations within the accounting profession by analyzing the case of financial statement manipulation perpetrated by PT Kimia Farma Tbk. A qualitative, descriptive research approach is employed to identify breaches of fundamental accounting ethics principles. The findings reveal that PT Kimia Farma Tbk. committed violations of four core ethical principles: integrity, objectivity, professional competence, and professional behavior. These violations were manifested in the overstatement of net income reported in the company’s 2001 financial statements. Such manipulative practices not only inflicted financial harm on investors and the public but also undermined the credibility of the accounting profession and eroded trust in the capital market.